Предмет: Математика,
автор: ajdarg472
r) 5 x – 13 = 3 X - 9
A) (5 x-6) -(4 x - 8) = 2
e) 6 ( X – 1,5) – 4 x= 2
>K) 0,9 x + 12 = 3
3) 7-2 ( x + 5) = 13 - 6 x
K) 4 (x -0,6) - 2 (x +0,2)= -2,6
JI) 5 ( x - 2) = 3 (5x – 13)
Ответы
Автор ответа:
1
Ответ:
решение на фотографии
Приложения:
Автор ответа:
0
Ответ:
r 2
a 0
e 5,5
>k -10
з 4
k 0,1
Ji 29
---
10
Похожие вопросы
Предмет: Английский язык,
автор: Nikita1234579
Предмет: Английский язык,
автор: olgaumchq
Предмет: Русский язык,
автор: nastenkamayantseva
Предмет: Алгебра,
автор: mark20041017
Предмет: Геометрия,
автор: Сабухи1